2020
DOI: 10.1002/ejp.1586
|View full text |Cite
|
Sign up to set email alerts
|

Association of quantitative sensory testing parameters with clinical outcome in patients with lumbar radiculopathy undergoing microdiscectomy

Abstract: Background/Aim: This study aimed to establish the somatosensory profile of patients with lumbar radiculopathy at pre-and post-microdiscectomy and to explore any association between pre-surgical quantitative sensory test (QST) parameters and post-surgical clinical outcomes. Methods: A standardized QST protocol was performed in 53 patients (mean age 38 ± 11 years, 26 females) with unilateral L5/S1 radiculopathy in the main pain area (MPA), affected dermatome and contralateral mirror sites and in age-and gender-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…QST can differentiate between cervical radicular pain and nonspecific neck pain 49 . As patients with predominant nerve root adhesions had an increased long‐term benefit from nerve root adhesiolysis, objective measurement of radicular pain and sensory function may be predictive of postsurgery clinical pain outcome 50,51 …”
Section: Discussionmentioning
confidence: 99%
“…QST can differentiate between cervical radicular pain and nonspecific neck pain 49 . As patients with predominant nerve root adhesions had an increased long‐term benefit from nerve root adhesiolysis, objective measurement of radicular pain and sensory function may be predictive of postsurgery clinical pain outcome 50,51 …”
Section: Discussionmentioning
confidence: 99%
“…Another four patients showed isolated hypersensitivity to one modality (brush or cold perception), with hyposensitive responses to all other tests. While hypersensitivity phenomena were common in one report with qualitative type testing study [18], some other studies with QST report hypersensitivity as a rare finding [17,19,20]. Some other radiculopathy studies did not record hypersensitivity or included them in the general group of "sensory impairments" [9].…”
Section: Discussionmentioning
confidence: 99%
“…The current perception threshold testing was evaluated in patients with lumbar radiculopathy before and after epidural steroid injection [27] without correlation in pain intensity changes after the treatment. Later studies with QST showed some potential to predict improvement after epidural steroid injection for sciatica-related pain [28] and in predicting functional status after microdiscectomy in patients with LSR [20]. QST could potentially reveal the treatment implicated mechanism of action of spinal manipulative therapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with detected hyposensitivity in various modalities represent the largest part (69.4%) of the whole study population, and this corresponds to the findings of the other studies. 9,[15][16][17][18][19] In addition, QualST showed that patients vary in the dysfunction of different axon types. The most common dysfunction was hyposensitivity to tactile static testing (Ab fibers).…”
Section: Discussionmentioning
confidence: 99%